Evaluation of a digital drainage system (Thopaz) in over 250 cases at a single site: A retrospective case‐control study. (22nd August 2017) - Arai, Hiromasa; Tajiri, Michihiko; Kameda, Yohei; Shiino, Kimihisa; Ando, Kohei; Okudela, Koji; Masuda, Munetaka
Abstract: Purpose: The aim of this study was to evaluate the efficacy of the Thopaz system, a new drainage system in management of general thoracic surgery, based on a review of our clinical practice and a comparison of the utility of the Thopaz device compared with a standard drainage system. Methods: A review of 540 thoracic surgeries at our hospital was performed. These cases were divided into 275 treated with the Thopaz system from April 2014 to March 2015 and 265 treated with a standard system from April 2013 to March 2014. The characteristics of patients and outcomes after surgery were compared in these 2 groups. Results: The characteristics of the patients were similar in the 2 groups. Outcomes after surgery, including types of operation, period of chest tube placement, chest tube reinsertion rate and clamping test rate also did not differ significantly between the groups. Conclusions: The non‐inferiority of the Thopaz system compared to a standard system was verified statistically. With advantages of providing objective data as a small portable system, in addition to the quietness of the unit and the ease of setup and operation, Thopaz system is likely to become mainstream in postoperative management in general thoracic surgery.